Isotopic coherence of refractory inclusions from CV and CK meteorites: Evidence from multiple isotope systems. (1st May 2018) - Shollenberger, Quinn R.; Borg, Lars E.; Render, Jan; Ebert, Samuel; Bischoff, Addi; Russell, Sara S.; Brennecka, Gregory A.
Abstract: Calcium-aluminum-rich inclusions (CAIs) are the oldest dated materials in the Solar System and numerous previous studies have revealed nucleosynthetic anomalies relative to terrestrial rock standards in many isotopic systems. However, most of the isotopic data from CAIs has been limited to the Allende meteorite and a handful of other CV3 chondrites. To better constrain the isotopic composition of the CAI-forming region, we report the first Sr, Mo, Ba, Nd, and Sm isotopic compositions of two CAIs hosted in the CK3 desert meteorites NWA 4964 and NWA 6254 along with two CAIs from the CV3 desert meteorites NWA 6619 and NWA 6991. After consideration of neutron capture processes and the effects of hot-desert weathering, the Sr, Mo, Ba, Nd, and Sm stable isotopic compositions of the samples show clearly resolvable nucleosynthetic anomalies that are in agreement with previous results from Allende and other CV meteorites. The extent of neutron capture, as manifested by shifts in the observed 149 Sm- 150 Sm isotopic composition of the CAIs is used to estimate the neutron fluence experienced by some of these samples and ranges from 8.40 × 10 13 to 2.11 × 10 15 n/cm 2 . Overall, regardless of CAI type or host meteorite, CAIs from CV and CK chondrites have similar nucleosynthetic anomalies within analytical uncertainty. We suggest the region that CV and CK CAIs formed was largely uniform with respect to Sr, Mo, Ba, Nd, and Sm isotopes when CAIs condensed and that CAIs hosted in CV and CK meteorites are derived from the same isotopic reservoir.